(untitled) (Herald of Journalism, 2020)
This article is about the role and reputation of journalism in today’s so ciety. Analysis of investigation is on this issue was the basis of this article. Public opinion survey showed that the reputation of journalism in Ka zakhstan is low. It has been proven that the journalists themselves are not particularly interested in journalism, interest fell study in this field.